Nanosheet composed of gold nanoparticle/graphene/epoxy resin based on ultrasonic fabrication for flexible dopamine biosensor using surface-enhanced Raman spectroscopy - Hussein, Mahmoud A.; El-Said, Waleed A.; Abu-Zied, Bahaa M.; Choi, Jeong-Woo (Nano convergence, 2020)
Construction of a fast, easy and sensitive neurotransmitters-based sensor could provide a promising way for the diagnosis of neurological diseases, leading to the discovery of more effective treatment methods. The current work is directed to develop for the first time a flexible Surface-Enhanced Raman Spectroscopy (SERS) based neurotransmitters sensor by using the ultrasonic-assisted fabrication of a new set of epoxy resin (EPR) nanocomposites based on graphene nanosheets (GNS) using the casting technique. The perspicuous epoxy resin was reinforced by the variable loading of GNS giving the general formula GNS/EPR 1–5 . The designed products have been fabricated in situ while the perspicuous epoxy resin was formed. The expected nanocomposites have been fabricated using 3%, 5%, 10%, 15% and 20% GNS loading was applied for such fabrication process. The chemical, physical and morphological properties of the prepared nanocomposites were investigated by using Fourier transforms infrared spectroscopy, X-ray diffraction, Thermogravimetric analysis, Differential Thermal gravimetry, and field emission scanning electron microscopy methods. The GNS/EPR 1–5 nanocomposites were decorated with a layer of gold nanoparticles (Au NPs/GNS/EPR) to create surface-enhanced Raman scattering hot points. The wettability of the Au NPs/GNS/EPR was investigated in comparison with the different nanocomposites and the bare epoxy. Au NPs/GNS/EPR was used as a SERS-active surface for detecting different concentrations of dopamine with a limit of detection of 3.3 µM. Our sensor showed the capability to detect low concentrations of dopamine either in a buffer system or in human serum as a real sample.